The Effect of Butyric Acid Produced by Engineered E. coli Nissle 1917 on Treatment of Ulcerative Colitis - Park Young Tae; Taejung Kim; Kim, Young-Joo; Ham, Jungyeob (한국생물공학회, 2020)
Butyric acid belongs to short-chain fatty acids (SCFAs) and is the most plentiful metabolite derived from bacterial fermentation of carbohydrates such as dietary fibers in the intestine. Faecalibacterium prausnitzii (FP) is one of the most abundant bacteria in the human intestinal microbiota and regarded as a major effector in human intestinal health because of its anti-inflammatory effects. It produces butyric acid which has beneficial effect on human gut health. However, the extreme oxygen sensitivity has been a major obstacle to cultivate and study physiological characteristics of this organism. The genes encoding Butyryl-CoA dehydrogenase (BCD) and Butyryl-CoA: Acetate-CoA-transferase (BUT) in FP were cloned and expressed in E. coli to determine the effect of butyric acid production on intestinal health. According to the results of butyric acid production in wildtype E. coli expressing BCD, BUT or both, BCD was shown to be essential, while BUT was dispensable, for the production of butyric acid. The anti-inflammatory effects of butyric acid production were tested by administrating these strains into DSS-induced colitis model mice.